2017
DOI: 10.1002/biof.1398
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells and signaling pathways by resveratrol and pterostilbene

Abstract: In past decades, increasing evidence regarding cancer stem cells (CSCs) may account for carcinogenesis, tumor drug-resistant, and metastasis. CSCs are even considered as the root causes of tumor recurrence and metastases. Targeting CSCs may provide a new clue to cure cancer. Epidemiological and clinical studies have suggested that intake of dietary natural products may bring health benefits including lowering risk of cancer incidence. In this review, we have particularly focused on targeting signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 46 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…Resveratrol promotes sensitivity to radiation and can downregulate androgen receptor (AR). Several in vivo studies in mice have suggested that resveratrol inhibits generation and proliferation of spontaneous PCs and xenograft malignancies [20]. In our study, we discovered that resveratrol suppressed cell survival and enhanced cell death in TRAMP cells characterized by elevated ROS level.…”
Section: Discussionsupporting
confidence: 54%
“…Resveratrol promotes sensitivity to radiation and can downregulate androgen receptor (AR). Several in vivo studies in mice have suggested that resveratrol inhibits generation and proliferation of spontaneous PCs and xenograft malignancies [20]. In our study, we discovered that resveratrol suppressed cell survival and enhanced cell death in TRAMP cells characterized by elevated ROS level.…”
Section: Discussionsupporting
confidence: 54%
“…Several clinical trials are currently underway [NCT00721877, NCT00920803, NCT00433576, and NCT00578396]. Pterostilbene, a dimethylated derivative of resveratrol with a higher bioavailability and is more lipophilic, exerts more potent suppressive activity against CSCs and cancer metastasis [ 211 , 212 ].…”
Section: Targeting Lipid Metabolism As Novel Therapeutic Strategies Amentioning
confidence: 99%
“…In vitro, pterostilbene inhibited the proliferation of a variety of tumor cells, including stomach, lung, liver, oral cavity, pancreas, lymph, colon, prostate, breast, melanoma, leukemia, and myeloma tumor cells. In vivo, pterostilbene inhibited tumor occurrence and metastasis and showed almost no toxicity [44,45]. Manlio et al found that pterostilbene had a stronger ability to induce the apoptosis of chronic myeloid leukemia cells than resveratrol.…”
Section: Anti-tumor Activitymentioning
confidence: 99%